Developing Language and Literacy: Effective Intervention in the Early Years - Carroll, J; Bowyer-Crane, C; Duff, F; Hulme, C; Snowling, M (2011)
Developing Language and Literacy: Effective Intervention in the Early Years describes successful intervention programmes to improve the phonological skills, vocabulary, and grammar of young children at risk of reading difficulties. • Presents two structured intervention programmes to provide support for young children with language and literacy difficulties • Describes clearly how to improve the language and foundation literacy skills of young children in the classroom • Includes information about how to assess research, and how to monitor and design intervention strategies for use with individual children • Helps teachers to develop an understanding of the intervention and research process as a whole • Additional journal content to support this title is available click here. © 2011 John Wiley and Sons, Ltd.